Meningkatkan pemahaman konsep matematis melalui discovery learning berbantuan Geogebra - Maemunah, Siti; Fitriani, Nelly; Nurfauziah, Puji (IKIP Siliwangi, 2025)
This study sought to ascertain whether students' comprehension of mathematical topics had increased as a result of using Discovery Learning with GeoGebra. This study employed a mixed model with a convergent parallel design. 58 eighth-graders from SMP Negeri 5 Purwakarta served as the subjects. Two groups of students were created: an experimental group and a control group. Pretests, posttests, and student response surveys were used to gather data. The Mann-Whitney test, normality, and N-Gain were used to assess the data. According to the data, both groups improved in the moderate category; nevertheless, the experimental class's average N-Gain (0.51) was higher than the control class's (0.38). The Mann-Whitney test findings showed a significant difference (sig. 0.004 < 0.05). Thus, the GeoGebra-assisted discovery learning model enhances conceptual mathematical knowledge more effectively than conventional learning. Furthermore, learning that encourages active participation in discovering ideas is well-received by students.